Hubungan Tingkat Pengetahuan dengan Kepatuhan Diet pada Penderita Diabetes Mellitus Di Puskesmas Kereng Bangkirai: The Corellation of Knowledge Level With Diet Compliance in Diabetes Mellitus Patiients at Keeng Bangkirai Puskesmas - Massiani Massiani; Rizki Muji Lestari; Dita Wasthu Prasida (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2023)
Diabetes mellitus or DM is a collection of symptoms that arise in a person marked by an increase in blood glucose levels above the normal value. Indonesia is ranked 7th out of 10 countries with the highest number of sufferers, which is 11.3%. The purpose of this study was to determine the relationship between the level of knowledge and dietary compliance in patients with diabetes mellitus at the Kereng Bangkirai Health Center. Analytical descriptive with cross sectional approach. The population in this study were all DM patients in the working area of the Kereng Bangkirai Health Center. The sample in this study were 66 people with DM who were controlled at the Kereng Bangkirai Health Center with a side technique using purposive sampling. The data of this study taken using questionnaires and interviews after tabulating the existing data were analyzed using Chi Square test analysis. The results showed that there was a relationship between the level of knowledge and dietary compliance in patients with diabetes mellitus in the Kereng Bangkirai Health Center area. (With p value 0.000 <a 0.05). ) means that there is a relationship between knowledge and the level of adherence to diet therapy in Diabetes Mellitus patients. It is hoped that people with diabetes will always be able to adhere to the diet recommended by health workers to be able to sort out foods that can be eaten or not for people with diabetes.